ASME 2016 Internal Combustion Engine Division Fall Technical Conference 2016
DOI: 10.1115/icef2016-9359
|View full text |Cite
|
Sign up to set email alerts
|

Potential and Limitations of Dual Fuel Operation of High Speed Large Engines

Abstract: Interest is growing in using fully flexible diesel-gas dual fuel engines for power generation and propulsion on land and sea. Benefits such as the flexibility to adapt the type of fuel to the market situation, fail-safe operation and lower NOx emissions than diesel engines are convincing arguments for engine operators. However, diesel-gas engine concepts still suffer from lower efficiency than state-of-the-art monovalent diesel engines and spark ignited gas engines when operated in the corresponding fuel mode.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The diesel fuel was injected with a 4-hole injector nozzle with a common rail system. Further information on the measurement setup can be found in [17]. All measurements have been carried out without the use of EGR.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The diesel fuel was injected with a 4-hole injector nozzle with a common rail system. Further information on the measurement setup can be found in [17]. All measurements have been carried out without the use of EGR.…”
Section: Methodsmentioning
confidence: 99%
“…As mentioned previously, the advantages of the diesel ignited gas engine concept over the pure diesel engine are its fuel flexibility and lower NO x and soot emissions. Nevertheless, several disadvantages come hand in hand with greater fuel flexibility and have to be taken into account; these are outlined in [17]. The main disadvantage is that the efficiency is lower than with the pure gas engine.…”
Section: Dual Fuel Technologymentioning
confidence: 99%
“…The wide range injector technology on the diesel side allows energetic diesel fractions of 1%-100% in full load operation, cf. Kiesling et al 19 and Redtenbacher et al 20 Using the triangular mounting sleeve contour design, either three, six, or nine gas nozzle holes can be arranged suitably, whereby the ninehole design has proven to have the best results regarding efficiency and emissions with this engine, cf. Aßmus et al 16 and Redtenbacher et al 9 Figure 1 provides an overview of the possible arrangements of the nozzle holes, which are positioned around the diesel nozzle.…”
Section: Requirements and Boundary Conditionsmentioning
confidence: 99%
“…The main combustion chamber is equipped with at least one diesel injector that can both deliver a sufficient amount of fuel for full load in diesel mode and provide proper atomization as a pilot injector corresponding to ≈ 1% of the total supplied chemical energy. This functionality is maintained by either using a well-designed single-needle injector [51,52] or integrating two needles into one injection valve unit for different engine operational modes [53,54]. By contrast, Kawase et al [55] reported the use of two injectors, each for a specific purpose.…”
Section: Low-pressure Dual-fuel Enginesmentioning
confidence: 99%